PERANCANGAN BADGES DENGAN KONSEP TEMA PANCA MAHABUTHA - Ardiana, Dewa Putu Yudhi (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2020)
Gamification aims to increase motivation and user engagement. Gamification has many game mechanics, one of them is badges which aim to show the user's achievement when completed a task or goal. This study aims to design badges with the Panca Mahabutha concept. There are 5 badges that designed in this study, namely akasa, bayu, teja, apah, and perthiwi. Each badge will be obtained by the user after successfully completing his task. Each badge will function as opening the next level. The use of the concept of Panca Mahabutha in badges aims to preserve Balinese culture.